2020
DOI: 10.1293/tox.2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Sequential histological changes in the liver of medaka exposed to methylazoxymethaol acetate

Abstract: We performed a medaka bioassay for the carcinogenicity of methylazoxymethaol acetate (MAM-Ac) to examine the sequential histological changes in the liver from 3 days after exposure until tumor development. The medaka were exposed to MAM-Ac at a concentration of 2 ppm for 24 hours, and were necropsied at 3, 7, 10, 14, 21, 28, 35, 42, 49, 60, and 91 days after exposure. MAM-Ac induced four cases of hepatocellular adenoma and one case of hepatocellular carcinoma in 8 fish after 60 or 91 days of exposure. Histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In zebrafish, spontaneous seminomas have been relatively known, and chemically-induced seminomas have been reported following N-ethyl-N-nitrosourea, N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), or 7,12-dimethylbenz[a]anthracene (DMBA) treatments 6,7 . Conversely, in medaka (Oryzias latipes), spontaneous tumor development in organs other than the liver, including testis, is rare 8 , and the frequency of germ cell tumors in previous reports was 0% (0 out of 961 males and females in life-span studies on spontaneous tumor development) 9 and 0.26% (14 males and 12 females, including chemically exposed medakas, out of approximately 10,000 males and females in carcinogenesis studies) 2 . We encountered spontaneous testicular tumors in two adult medakas (Cases I and II).…”
mentioning
confidence: 91%
“…In zebrafish, spontaneous seminomas have been relatively known, and chemically-induced seminomas have been reported following N-ethyl-N-nitrosourea, N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), or 7,12-dimethylbenz[a]anthracene (DMBA) treatments 6,7 . Conversely, in medaka (Oryzias latipes), spontaneous tumor development in organs other than the liver, including testis, is rare 8 , and the frequency of germ cell tumors in previous reports was 0% (0 out of 961 males and females in life-span studies on spontaneous tumor development) 9 and 0.26% (14 males and 12 females, including chemically exposed medakas, out of approximately 10,000 males and females in carcinogenesis studies) 2 . We encountered spontaneous testicular tumors in two adult medakas (Cases I and II).…”
mentioning
confidence: 91%
“…Although the utility of these assays is limited for screening unknown chemicals for potential carcinogenicity, they serve as a shorter-term assay 39 and provide a more sensitive evaluation for hepatocarcinogens than assays with rodents 40 . In particular, the alkylating agents, diethylnitrosamine 41 and methylazoxymethaol 42 , induce liver tumors within just 2–3 months in medaka. The limited ability to repair DNA adducts in the medaka liver might be an important factor contributing to the high sensitivity for alkylating agent-induced hepatocarcinogenicity 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the alkylating agents, diethylnitrosamine 41 and methylazoxymethaol 42 , induce liver tumors within just 2–3 months in medaka. The limited ability to repair DNA adducts in the medaka liver might be an important factor contributing to the high sensitivity for alkylating agent-induced hepatocarcinogenicity 42 , 43 . In the present study, as the swim bladder tumors were observed from 13 dph and onwards, it was revealed that tumors in medaka developed in an extremely short-term period, not only in the liver but also in the swim bladder.…”
Section: Discussionmentioning
confidence: 99%